Technology for the formation of digital competencies of civil servants - Ovchinnikov, Svyatoslav Sergeevich (Социодинамика, 2024)
The subject of the research is the study of algorithms for the formation of competencies. The author examines various process structures of competence formation. The aim work is to develop a unified algorithm formation of digital competencies for civil servants. The specifics study will be focused on government civil servants who use digital technologies in their official activities. Special attention is paid to the issue of training and development of public civil servants. Author considers such an aspect of the topic as the impact of digital knowledge, skills and abilities on the digital economy of the Russian Federation. Author discusses various training technologies aimed at improving the qualification level of a civil servant. Author considers certain algorithmization of the formation of digital competencies in public administration. Features influence of educational activities on the creation of a special model of digital competencies of a civil servant. The following methods were used in the study: traditional analysis of documents (normative legal acts, scientific articles), modeling. As a result of the research author developed technology for the formation of digital competencies, aimed at developing the professional level of government civil servants and focused on the introduction of modern training models in public authorities. The area of possible implementation of the research results in such state bodies as the Government of the Russian Federation, the Administration of the President of the Russian Federation, the Ministry of Digital Development, Communications and Mass Media of the Russian Federation, etc. The novelty research is the development of completely new process of training and development of civil servants. The use of algorithmic technology for the formation of digital competencies will contribute to improving the qualification level of civil servant, improving public administration in a particular public authority, increasing measures to train and develop digital literacy of civil servant.